New Data on Armadillos (Xenarthra: Dasypodidae) for Central Patagonia, Argentina - Abba, Agustin Manuel (2010)
Armadillos represent the most diverse family of xenarthrans. Although many studies have been done on these mammals, several topics, such as their local distribution, natural history, behavioral ecology and conservation, remain poorly known. Chaetophractus villosus and Zaedyus pichiy are the most common armadillos in extra-Andean Patagonia, a vast area in southern Argentina and Chile that encompasses different ecosystems and has been modified by human activities, mainly by sheep grazing. In this work we present new data on the distribution, natural history, conservation, and ecology of C. villosus and Z. pichiy from central Patagonia (Chubut and Río Negro provinces, Argentina). We registered 60 localities for C. villosus and 35 for Z. pichiy that confirm their presence in wide sectors of central Patagonia. Furthermore, we confirmed that these two armadillo species suffer high rates of mortality due to their use as a protein source, hunting by dogs, road traffic, and poisoning, among others. We conclude that their populations are at risk of overexploitation and local extinction. The basic knowledge provided here will be a first step towards the conservation of these characteristic Patagonian mammals.